2017
DOI: 10.1007/s12032-016-0879-9
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, NRAS and BRAF mutations in colorectal cancer and melanoma

Abstract: Cancers are the group of diseases, which arise because of the uncontrolled behavior of some of the genes in our cells. There are possibilities of gene amplifications, overexpressions, deletions and other anomalies which might lead to the development and spread of cancer. One of the most dangerous ways to the cancers is the mutations of the genes. The mutated genes can start unstoppable proliferation of cells, their uncontrolled motility, protection from apoptosis, the DNA mutation enhancement as well as other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 105 publications
0
91
0
Order By: Relevance
“…Due to this, mutations, which cause constitutive activation of KRAS, lead to uncontrolled proliferation and other processes causing cancer development and spreading. KRAS can also regulate other signaling pathways, such as PI3K-AKT, PLC-PKC, and RAL, which are also known to be involved in cancer progression [13]. KRAS is mutated in more than 20% of human cancers, mostly in pancreatic (more than 90%), colorectal and lung cancers [13] as well as leukemias [14] (Table 1).…”
Section: Gene Mutations In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, mutations, which cause constitutive activation of KRAS, lead to uncontrolled proliferation and other processes causing cancer development and spreading. KRAS can also regulate other signaling pathways, such as PI3K-AKT, PLC-PKC, and RAL, which are also known to be involved in cancer progression [13]. KRAS is mutated in more than 20% of human cancers, mostly in pancreatic (more than 90%), colorectal and lung cancers [13] as well as leukemias [14] (Table 1).…”
Section: Gene Mutations In Pancreatic Cancermentioning
confidence: 99%
“…KRAS can also regulate other signaling pathways, such as PI3K-AKT, PLC-PKC, and RAL, which are also known to be involved in cancer progression [13]. KRAS is mutated in more than 20% of human cancers, mostly in pancreatic (more than 90%), colorectal and lung cancers [13] as well as leukemias [14] (Table 1). Mutations of the codons G12, G13, or Q61 are usually associated with constitutively active KRAS, and recurrent mutations in K117 and A146 seem to be additional hotspots (Figure 2).…”
Section: Gene Mutations In Pancreatic Cancermentioning
confidence: 99%
“…Several therapies targeting BRAF are currently in use or under investigation for the treatment of BRAF-mutant metastatic melanoma, including vemurafenib [approved by the Food and Drug Administration (FDA) in 2011], dabrafenib (FDA approved in 2013), and encorafenib (FDA approval pending) [8][9][10]. More recently, BRAF inhibitors are co-administered with inhibitors of MEK, another kinase downstream of BRAF in the same signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 4A illustrates the genetic interaction subnetwork that contains 82 significantly mutated network-predicted genetic interactions for SKCM and 78 known literature-derived genetic interactions connecting 84 genes (S4 Table). KRAS, encoding the human cellular homolog of a transforming gene isolated from the Kirsten rat sarcoma virus, plays essential roles in multiple cancer types, including melanoma [25,26]. Here, we identified that KRAS showed multiple significant genetic interactions with BACH2 (q = 0.005, Fig 4B), TAOK1 (q = 0.006), and NF1 (q = 0.04).…”
Section: Plos Computational Biologymentioning
confidence: 86%